Shining light on darkness: suicidal ideation and suicide attempt among Iranian women who do and do not use drugs - Ghaderi, Salahedin; Morovat, Borzoo; Masoumirad, Reza; Noori, Roya; Saeedi Moghaddam, Sahar; Moazen, Babak; Dolan, Kate; Shokoohi, Mostafa (Drugs, 2021)
Illicit drug use and dependence is a well-established risk factor for self-harm and suicide. The present comparative study aimed to evaluate the prevalence of suicidal ideation and suicide attempt among Iranian women. With a cross-sectional design, a total of 787 Iranian women who reported using illicit drugs and 406 women without drug use history were recruited and invited to answer questions regarding their socio-demographic status, individual health conditions, interpersonal information, e.g. experience of sexual, verbal, or physical violence, illicit drug use, and history of suicidal ideation and suicide attempt. Data were collected through gender-matched interviews. Generalized Linear Models (GLM) with Poisson family and log link function were used to report adjusted prevalence ratios (APR) of the associated factors of the study outcomes. The mean age (SD) of women with and without drug use was 34.3 (9.2) and 30.5 (11.0) years, respectively. Prevalence of lifetime history of both suicidal ideation (38.54 vs 19.01%) and suicide attempt (26.25 vs 6.55%) was significantly higher among women reporting drug use compared to those reporting no drug use. The APR of the associated factors ranged from 1.8 to 3.1 and from 3.3 to 4.8 for suicidal ideation and suicide attempt, respectively. Women who use drugs are at greater risk of suicidal ideation and suicide attempt compared with their peers who do not use drugs. Although further studies are required to explore possible causal relationships between drug use and suicide among Iranian women, a comprehensive package of care and treatment in addition to predominantly drug-related harm reduction programs may help address such critical health issues among Iranian women who use drugs.